Development of a new chlamydiales-specific real-time PCR and its application to respiratory clinical samples - Lienard, Julia; Croxatto, Antony; Aeby, Sebastien; Jaton, Katia; Posfay-Barbe, Klara; Gervaix, Alain; Greub, Gilbert (Journal of clinical microbiology, 2011)
Originally composed of the single family Chlamydiaceae, the Chlamydiales order has extended considerably over the last several decades. Chlamydia-related bacteria were added and classified into six different families and family-level lineages: the Criblamydiaceae, Parachlamydiaceae, Piscichlamydiaceae, Rhabdochlamydiaceae, Simkaniaceae, and Waddliaceae. While several members of the Chlamydiaceae family are known pathogens, recent studies showed diverse associations of Chlamydia-related bacteria with human and animal infections. Some of these latter bacteria might be of medical importance since, given their ability to replicate in free-living amoebae, they may also replicate efficiently in other phagocytic cells, including cells of the innate immune system. Thus, a new Chlamydiales-specific real-time PCR targeting the conserved 16S rRNA gene was developed. This new molecular tool can detect at least five DNA copies and show very high specificity without cross-amplification from other bacterial clade DNA. The new PCR was validated with 128 clinical samples positive or negative for Chlamydia trachomatis or C. pneumoniae. Of 65 positive samples, 61 (93.8%) were found to be positive with the new PCR. The four discordant samples, retested with the original test, were determined to be negative or below detection limits. Then, the new PCR was applied to 422 nasopharyngeal swabs taken from children with or without pneumonia; a total of 48 (11.4%) samples were determined to be positive, and 45 of these were successfully sequenced. The majority of the sequences corresponded to Chlamydia-related bacteria and especially to members of the Parachlamydiaceae family.